Contaminations between concepts: a look at creation and thought with Gustav Mahler (Palíndromo, 2022)
This article deals with experience, thinking and creation, recognizing that the themes are broad, complex, and suggest many paths. Thus, we seek intertwining between such concepts in three topics, making three relationships between: a) experience and creation; b) creation and invention; and, finally, c) creation and thought, a search for tunings with Gustav Mahler. We try to move these concepts, dialoguing with the theories of Andrei Tarkovsky (2010), Marilena Chaui (1995, 2002), Jorge Larrosa Bondia (2002) and George Steiner (2003), among others. A clipping to also think about these concepts, that is, possible listening, which would be the tunings with the work of Mahler (1860-1911). Finally, in the company of this austrian czech conductor and composer, I venture a brief dialogue, tuning with the artist's career, in a cooperative look to think about the connections between the concepts of experience, invention, thought and creation. The three topics I chose allowed me to think about the dynamic character that surrounds creation and its processes. The reading of Steiner, Tarkovsky among others, brings us to different rather than new conceptions of creation processes - both the existence of an ontological value of creation and its universality can be questioned as historically localizable ideologies. Thus, the crossings of writing and text creation oscillate between the personal experience of artists cut out for this text and the theoretical interrogations caused by such cutouts. I sought to investigate creation as experience, a sometimes nervous structure of consciousness when we communicate with ourselves and others, especially in the field of art.
Keywords: Contamination between concepts; Creation and Thinking with Gustav Mahler; Experience and Creation; Creation and Invention; Experience, thought and creation